UPAYA UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES (UNHCR) DALAM MENANGANI MASALAH PENGUNGSI ROHINGYA DI PROVINSI ACEH TAHUN 2020-2023 - Hasanah, Nur; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study examines the dynamics of handling Rohingya refugees in Aceh Province from 2020 to 2023, focusing on social, political, humanitarian, and inter-agency coordination aspects. The increasing influx of arrivals has made Aceh Province a major transit area for Rohingya refugees fleeing the conflict and humanitarian crisis in Myanmar. This study examines the roles of UNHCR, local governments, NGOs, and local communities in responding to the crisis through various stages, from emergency rescue and registration to placement and relocation planning to more centralized shelters. The research method used was a qualitative approach with descriptive analysis of official documents, humanitarian organization reports, and other secondary data. This study utilizes a liberal institutionalism perspective, which refers to the state requiring a specific organizational role in addressing a phenomenon. This perspective is then developed using international organization theory, focusing on UNHCR's efforts to respond to, address, and resolve the Rohingya refugee crisis in Aceh Province. The results of this study indicate that UNHCR's efforts to address the Rohingya refugee problem in Aceh Province encompass several aspects, including providing basic protection, registering and determining refugee status, providing basic assistance such as shelters and healthcare during the pandemic, and working collaboratively with international institutions, local governments, and NGOs. These efforts emphasize refugee protection while implementing humanitarian policies as a means of protection for refugees, developed by international organization theory. These efforts are said to be effective in protecting the rights of Rohingya refugees in Aceh Province, but they still face challenges such as limited legal protection, a lack of human resources, and resistance from the local community. Keywords: Rohingya refugees, UNHCR, Aceh Government, humanitarian crisis